Solvability for a New Class of Moore-Gibson-Thompson Equation with Viscoelastic Memory, Source Terms, and Integral Condition - Salah Mahmoud Boulaaras; Abdelbaki Choucha; Djamel Ouchenane; Asma Alharbi; Mohamed Abdalla; Bahri Belkacem Cherif (Journal of Function Spaces)
This paper deals with the existence and uniqueness of solutions of a new class of Moore-Gibson-Thompson equation with respect to the nonlocal mixed boundary value problem, source term, and nonnegative memory kernel. Galerkin’s method was the main used tool for proving our result. This work is a generalization of recent homogenous work.